Pengaruh Self Assessment System Terhadap Tax Evaison - Teguh Erawati; Riranti Desinta Pawestri (Universitas Nusantara PGRI Kediri, 2022)
Tax is a mandatory public contribution to state revenues based on the law (can be imposed) by not receiving reciprocal services (contra-achievements) that can be directly shown and which can be used to pay for general state expenditures. This study aims to prove the effect of applying the Self Assessment Tax System to tax evasion actions. This research is motivated by the many cases that occur in this country regarding public actions and the lack of public awareness related to the level of compliance in taxation which is often a burden for taxpayers because it will reduce income so many taxpayers want low tax payments through tax avoidance. (tax avoidance) and acts of tax evasion (tax evasion). This study uses a descriptive or explanatory research method that uses a quantitative approach. The population of this study is all individual taxpayers (WPOP) registered with the Tax Service Office (KPP) Pratama Bantul. The samples taken in this study were individual taxpayers, other professional freelancers and entrepreneurs who were registered at the Tax Service Office (KPP) Pratama Bantul. Sampling was done using random sampling method. The results of this study can be concluded that the variable Self assessment system and tax audit has no effect on tax evasion.